Tempol maintained the cellular integrity of the cerebellar cortex by preserving neuron survival, autophagy, glial cells, and synapses after cisplatin exposure - Amal S. Sewelam; Mohammed A.S. Amin; Shaimaa R. Abdelmohsen; Osama A. Mohammed; Abdullah A. Hashish; Jaber Alfaifi; Adel M. Aboregela (Elsevier, 2024)
Background: tempol is a free radical scavenger that passes through the blood-brain barrier. This study aimed to assess its ameliorative role in the cerebellar cortex after cisplatin injection. Methods: the examined forty-eight adult male wistar albino rats were divided into four groups. The saline group received 0.5 ml of normal saline, the tempol group was injected with 0.5 ml of tempol (100 mg/kg/day), the cisplatin group was injected with cisplatin single dose (7 mg/kg) on the 8th day, and cisplatin + tempol group received combined treatment. All groups were dosed through intraperitoneal injections. Results: histological examination revealed meningeal congestion and thickening with excess collagen, discrete vacuolated cortical cells, with pyknotic nuclei, and tissue loss after cisplatin. Immunohistochemical expression of NF-kβ and GFAP were enhanced, while LC3-II and synaptophysin expression decreased with cisplatin. Cisplatin treatment reduced mRNA expression of NGF, GLP-1, BDNF, PGC1-α, and PPAR-α while it boosted Caspase-3 expression. Moreover, it tripled the level of MDA and lowered levels of SOD, CAT, and GSH in cerebellar tissue homogenate. Tempol supplementation restored the meningeal and the normal histological structure of the cerebellar cortex. The immunohistochemical as well as mRNA expressions of different genes were highly normalized but still showed variable significant differences when compared to the control except for NGF, PGC1-α, and Caspase-3 genes. Great restoration of biochemical markers was evident with tempol, especially for CAT that showed no significant difference in comparison with the saline group. Conclusion: tempol cisplatin combination can enhance neuronal survival, promote autophagy, decrease astrogliosis, and preserve synapses.